6(2x-3)-3x=5x+8

Simple and best practice solution for 6(2x-3)-3x=5x+8 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(2x-3)-3x=5x+8 equation:


Simplifying
6(2x + -3) + -3x = 5x + 8

Reorder the terms:
6(-3 + 2x) + -3x = 5x + 8
(-3 * 6 + 2x * 6) + -3x = 5x + 8
(-18 + 12x) + -3x = 5x + 8

Combine like terms: 12x + -3x = 9x
-18 + 9x = 5x + 8

Reorder the terms:
-18 + 9x = 8 + 5x

Solving
-18 + 9x = 8 + 5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5x' to each side of the equation.
-18 + 9x + -5x = 8 + 5x + -5x

Combine like terms: 9x + -5x = 4x
-18 + 4x = 8 + 5x + -5x

Combine like terms: 5x + -5x = 0
-18 + 4x = 8 + 0
-18 + 4x = 8

Add '18' to each side of the equation.
-18 + 18 + 4x = 8 + 18

Combine like terms: -18 + 18 = 0
0 + 4x = 8 + 18
4x = 8 + 18

Combine like terms: 8 + 18 = 26
4x = 26

Divide each side by '4'.
x = 6.5

Simplifying
x = 6.5

See similar equations:

| 9x^2+4y^2-8y-32=0 | | 5x=-3.7 | | 7x-5=27 | | 9y=5y+5-9 | | An+c=5 | | b/8=9/5 | | 7x-2=7-17 | | 3l+6=p | | 2(y-5)-5=3 | | (x/4)-2x=2 | | (27/3)=-8x | | 576=(3x+20)+5(.65x)+(.5x) | | 576=(3x+20)+5(.65x)+(.5x) | | Y=3y-a | | 3(3p+4)-4(p+8)= | | 16x+24=16x+24 | | .25(3x-16)+.25x=5.333 | | -2.3-3y-2.5-y=-3y-3.6 | | 4(x+3)=2x+74 | | Log(x+3)=2.1 | | 78+2x=100 | | 6(3b-8)=2(6b-3) | | 15+3m=27 | | -6.3-3z-1.5-z=-3z-5.9 | | 4b+b^2=0 | | -1x^1+1= | | .20x+.35(30)=29.5 | | 4(x-10)=-6(x-2)-6 | | (-2a/b^4)^2 | | .20+.35(30)=29.5 | | y=x^2+2ax+4 | | .355=(×^×)/((2.82-2×)(2.83-2×)(2.83-×) |

Equations solver categories